Analisis Kinerja Keuangan Klinik Husada Mulia Kabupaten Lumajang - Emmy Ermawati (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2018)
Husada Mulia Clinic is a private health clinic located in Lumajang. The financial analysis at this clinic initially only used fee for service method and then cooperated with JKN with capitation claim method for outpatient, Husada Mulia Clinic of Lumajang Regency should be able to adjust the strategy with existing health regulation condition. Therefore, financial performance monitoring is carried out every period to be able to manage the process of providing health services to the community in accordance with the standards. The conclusion obtained in this study is the current ratio of Financial Performance Clinic Husada Mulia Lumajang is considered high. This is the same with the debt to asset ratio and ROI of the Husada Mulia Clinic Financial Performance of Lumajang Regency is considered high. While Total Asset Turnover from Financial Performance Clinic Husada Mulia Lumajang regency is considered low. From the results of this conclusion is expected to assist the relevant parties in determining the next policy so as to improve service to the community.